Apakah nilai kerja pekerja kilang? - Kasa, Zakaria (Universiti Putra Malaysia Press, 2005)
The purpose of this study was to determine the work values among factory workers in the district of Hulu Langat, Selangor. A total of 451 factory workers were randomly selected as the sample of the study. Questionnaires were used to collect the data pertaining to the background and work values of the respondents. The findings showed that factory workers assumed that job security, career development, economic rewards, workplace condition, creativity, life style, relation with other workers were important to them. Autonomy and prestige were not so important to them. In addition, the data showed that there was a significant different between male workers and female workers in the values of creativity, relation with other workers and autonomy. Male workers were found to regard these values as more important to them compared to female workers.